2019
DOI: 10.1016/j.apgeochem.2019.104438
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm-scale biogeochemical stabilization of Pb, As, Ba and Zn in mine tailings amended with manure and ochre

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 55 publications
4
25
0
Order By: Relevance
“…The NH4NO3-extractable Fe concentration was low for P0% (0.02 µg.g -1 ), and only increased following the ochre amendment (27-fold) (Table 2), and can be explained by the NH4NO3-extractable Fe concentration of the ochre (1.04 µg.g -1 ) (Table 1). Such elevated Fe content in the ochre has been previously observed by Abed et al ( 2017) , Doi et al (2005) and Thouin et al (2019). However, one surprising fact was that although NH4NO3-extractable Fe concentration in manure was high (2.41 µg.g -1 ), no increase was observed following its addition to the Pontgibaud technosol, maybe due to its low application rate.…”
Section: Field Code Changedsupporting
confidence: 66%
See 2 more Smart Citations
“…The NH4NO3-extractable Fe concentration was low for P0% (0.02 µg.g -1 ), and only increased following the ochre amendment (27-fold) (Table 2), and can be explained by the NH4NO3-extractable Fe concentration of the ochre (1.04 µg.g -1 ) (Table 1). Such elevated Fe content in the ochre has been previously observed by Abed et al ( 2017) , Doi et al (2005) and Thouin et al (2019). However, one surprising fact was that although NH4NO3-extractable Fe concentration in manure was high (2.41 µg.g -1 ), no increase was observed following its addition to the Pontgibaud technosol, maybe due to its low application rate.…”
Section: Field Code Changedsupporting
confidence: 66%
“…Finally, the results showed that SPW pH increases were higher when amendments were combined than when they were applied alone, showing neutral values compared to the slightly acidic values still observed with single amendment application. Such increases in SPW pH following biochar, ochre and/or manure amendments have previously been observed and attributed to the alkalinity of the three amendments (Marques et al 2008, Olimah et al 2015, Van Poucke et al 2018, which induces a liming effect. Indeed, biochar, ochre and manure presented alkaline pH values of 8.46, 8.29 and 9.52, respectively.…”
Section: Field Code Changedsupporting
confidence: 53%
See 1 more Smart Citation
“…Organic wastes provide the nutrients necessary for plant growth, while marble wastes tend to increase pH, enhancing the immobilization of metal contaminants. To fully understand the influence of amendments on the behavior of metal contaminants, Thouin et al (2019) set up an original leaching experiment on mine tailings configured to be close to real conditions. The dynamic of natural recharge was reproduced by a regular water supply (every week).…”
Section: Journal Pre-proofmentioning
confidence: 99%
“…Apart from a slight increase in Pb concentration during the first half of the experiment, a decrease to the base level during the rest of the experiment was recorded. Therefore, Thouin et al (2019) identified promising amendments to reduce Pb mobility in contaminated tailings. Nevertheless, this experiment, though critical for understanding these systems, was essentially qualitative as the nature and the rate of the main biogeochemical processes involved in the immobilization of Pb remain unknown.…”
Section: Journal Pre-proofmentioning
confidence: 99%